Hypoxic mesenchymal stem cells (MSCS)-induced interleukin (IL)-10 alleviate systemic lupus erythematosus (SLE) infl ammation through inhibiting interferon (IFN)-gamma production - Yan Wisnu Prajoko; Agung Putra; Ardi Prasetio; Nur Amalina (Medicinski glasnik, 2023)
Aim: To determine the eff ect of hypoxic mesenchymal stem cells (MSCs) on the interleukin (IL)-10 and interferon (IFN)-gamma in peripheral blood mononuclear cells (PBMCs) from systemic lupus erythematosus (SLE) patients. Methods: This study used a post-test control group design. Hypoxic MSCs were isolated and characterized according to their surface marker expression and diff erentiation capacities. PBMCs isolated from SLE patients were divided into three groups: control and two treatment groups. The treatment groups were treated by co-culturing MSCs to PBMCs with a ratio of 1:10 (T1) and 1:1 (T2) for 48 h incubation. Furthermore, IFN-gamma and IL-10 levels were determined by cytometric bead array (CBA) fl ow cytometry. Results: Hypoxic MSCs signifi cantly decreased the IFN-gamma levels and increased the IL-10 levels in dose-dependent manner compared to the control group. The highest activity of hypoxic MSCs was noticed in T2 group. Conclusion: Hypoxic MSCs- induced IL-10 are important in the control of anti-infl ammatory eff ect on SLE through inhibiting IFN-gamma.
Keywords: hypoxic MSC; IFN-gamma; IL-10; infl ammation; PBMC; SLE